Instillation of Pancasila Values (Sila-3) in PPKn Learning in Students at SMK Negeri 2 Lubuk Basung, Agam District - Risna, Avifah; Jaenam, Jaenam; Asril, Asril (CV. Rayyan Dwi Bharata, 2022)
This research is motivated by the problems that occur in schools that students at SMK N 2 Lubuk Basung still tend to do things that are not in accordance with the values of Pancasila, especially the value of unity among students. Some of these problems include there are still students who distinguish friends, do Body shaming. Lack of togetherness and cohesiveness of students, there are still many students who have not applied the attitude of the form of practicing the value of unity in learning activities in the classroom and outside the classroom. This type of research is a descriptive qualitative research. With data collection techniques, namely observation, interviews and documentation. The data triangulation carried out is source triangulation, technique triangulation and time triangulation. And data analysis techniques are data reduction, data presentation and verification/conclusion. The results of this study explain that: 1) teachers design and prepare learning tools and teaching modules. This learning design is to achieve the specified Learning Outcomes (CP). 2) the inculcation of the value of unity in Civics learning in students is instilled through 3 aspects of education, namely aspects of knowledge, aspects of attitudes and psychomotor aspects. 3) the teacher's obstacle and solution in instilling the value of unity in Civics learning in students is that there are still students who have not applied the value of unity in the school environment but this can be handled well by the teacher by the teacher instilling in students a sense of kinship and instilling a sense of belonging. love the homeland. Conclusion The results of this study are teachers are able to design learning about the value of unity and apply it in the form of 3 aspects, namely aspects of knowledge, aspects of attitudes and psychomotor so that obstacles to the value of unity against students can be overcome.